Decarbonizing university campuses through the production of biogas from food waste: An LCA analysis. (October 2021) - Zhou, Hewen; Yang, Qing; Gul, Eid; Shi, Mengmeng; Li, Jiashuo; Yang, Minjiao; Yang, Haiping; Chen, Bin; Zhao, Haibo; Yan, Yunjun; Erdoğan, Güneş; Bartocci, Pietro; et al.
Abstract: The amount of food waste production in China catering industry is approximately 17–18 Mt per year. This sector accounts for about 20% of the total food losses in China. China's National Development and Reform commission has ratified 100 pilot cities in five batches to implement food waste treatment projects. Almost the 80% of these projects is based on anaerobic digestion. So, it is very important to understand clearly which is the environmental impact of these new bioenergy, or waste to energy, chains (especially at a small scale). For this reason, a Life Cycle Assessment case study is presented in this work, based on an anaerobic digestion plant, fed with the non edible food waste produced by 29 canteens, which operate inside the campus of the Huazhong University of Science and Technology (HUST). The analyzed impacts are: Climate Change, Acidification, Eutrophication, and Photochemical Oxidation. The functional unit is represented by 1 kWh of produced electricity. This work demonstrates that small scale biogas plants can be realized inside big Chinese University campuses and can efficiently reduce the environmental impact of food waste management, especially if the pyrolysis process is coupled to dispose the digestate.